Relating Phylogenetic and Functional Diversity among Denitrifiers and Quantifying their Capacity to Predict Community Functioning - Falcão Salles, Joana; Le Roux, Xavier; Poly, Franck (Frontiers in Microbiology, 2012)
Genetic diversity of phylogenetic or functional markers is widely used as a proxy of microbial diversity. However, it remains unclear at what extent functional diversity, gene sequence diversity and community functioning are linked. We analysed, for a range of denitrifying bacteria, the relationships between (i) the similarity of functional traits evaluated from metabolic profiles (BIOLOG plates) or from N2O accumulation patterns on different C sources, and (ii) the similarity of phylogenetic (16S rRNA gene) or functional (nir gene) markers. We also calculated different proxies for the diversity of denitrifier community based on taxa richness, phylogenetic or functional similarities, and evaluated their performance in inferring the functioning of assembled denitrifying communities. For individual strains, the variation in the 16S rRNA gene sequence explained only 10% of the variation in metabolic patterns and were not related to N2O accumulation. The latter was correlated with the similarity of nitrite reductase residues. When nir genes were analysed separately, the similarity in amino acids coded by the nirS genes accounted for 48% of the variance of the observed pattern of N2O accumulation, whereas nirK amino acid residues were unrelated to N2O accumulation. For bacterial assemblages, phylogenetic diversity and mean community dissimilarity, calculated using 16S rRNA gene sequences, and functional diversity measures associated with BIOLOG, predicted poorly the variation in the functioning of assembled communities (below 15%). In contrast, the proxies of functional diversity based on N2O accumulation patterns performed better and explained from 23 to 42% of the variation in community functioning. Amongst those, community niche was the best metric, indicating the importance of complementarity for carbon resources among taxa in the context of denitrification.